Chemoprotective Effects of Propolis on Aflatoxin BI-Induced Hepatotoxicity in Rats: Oxidative Damage and Hepatotoxicity by Modulating TP53, Oxidative Stress - Yilmaz, Seval; Kandemir, Fatih Mehmet; Kaya, Emre; Ozkaraca, Mustafa (Bentham Science Publ Ltd, 2020)
Objective: This study aimed to detect hepatic oxidative damage caused by aflatoxin B1 (AFB1), as well as to examine how propolis protects against hepatotoxic effects of AFB1. Methods: Rats were split into four groups as control group, AFB1 group, propolis group, AFB1-1 propolis group. Results: There was significant increase in malondialdehyde (MDA) level and tumor suppressor protein (TP53) gene expression, Glutathione (GSH) level, Catalase (CAT) activity, CAT gene expression decreased in AFB1 group in blood. MDA level and Glutathione-S-Transferase (GST) activity, GST and TP53 gene expressions increased in AFB I group, whereas GSH level and CAT activity alongside CAT gene expression decreased in liver. AFB1+propolis group showed significant decrease in MDA level, GST activity, TP53 and GST gene expressions, GSH level and CAT activity and CAT gene expression increased in liver compared to AFB1 group. Conclusion: These results suggest that propolis may potentially be natural agent that prevents AFB1-induced oxidative stress and hepatotoxicity.
Keywords: Aflatoxin B1; oxidative stress; antioxidant; tumor suppressor protein; MDA; GSH